A parametric numerical study on the behavior of large precast tunnel segments during TBM thrust phase. (15th August 2021) - Trabucchi, Ivan; Tiberti, Giuseppe; Plizzari, Giovanni A.
Graphical abstract: Abstract: During the last two decades, Fiber Reinforced Concrete (FRC) was adopted in several segmental tunnel linings. The benefits related to the inclusion of fiber reinforcement in cementitious composites are mainly related to the increase of post-cracking tensile residual properties. FRC allows to reduce or avoid conventional reinforcement leading to a more efficient segment production process. The application of Tunnel Boring Machine (TBM) thrust jack forces during the lining construction stage is one of the most demanding loading conditions, since high-concentrated forces are introduced in last installed segments, especially for large diameter lining. Hence, special attention should be devoted to this phase by considering parameters which may affect segment structural response. To this aim, the behavior of a lining having large diameter during TBM operations was investigated by means of a broad parametric numerical study concerning segment configuration, irregularities and lining slenderness. The following reinforcement solutions were also considered: traditional steel rebars only, steel fibers reinforcement only and a combination of them (hybrid solution). The study clearly proved that segment configurations as well as irregularities strongly affect the structural behavior of segments. The hybrid reinforcement or FRC only solution having high post-cracking performance may guarantee the same response of RC solution.